Turubamba cultural park: a process developed from, for and with the people - Vicente Correa, Christian Fernando; Rivera Moyano, Pamela Suhan (Conexiones UG, 2024)
Since 2013, the former Civil Registry of Turubamba, in the south of the Metropolitan District of Quito, closed its doors due to alleged structural damage. organized neighbors, from different disciplines and leadership positions, began to carry out activities with the objective of activities with the objective of giving a good use to the property, which had been a focus of insecurity, unhealthy of insecurity, unhealthiness and bad urban image, and that due to its extension, enclosures and shape, it was an urban edge. and shape, it was an urban edge. As part of the community's actions, the following were carried out peaceful takeovers of the space, marches, fairs, among other activities. Integral Architecture, one of the collectives that are part of the group of managers of the the process, we propose to generate a study of the urban reality of the sector, along with a technical, administrative and administrative technical, administrative and social information gathering, through work tables, surveys in collaboration with the Faculty of Architecture and Urbanism of the Central University of Ecuador. of Architecture and Urbanism of the Central University of Ecuador, where it was concluded that the best option would be a recreational - cultural cultural and recreational equipment, having later hearings and roadmaps with authorities, the construction of the Turubamba Cultural Park, inaugurated by the Municipality of the Metropolitan District of Municipality of the Metropolitan District of Quito on October 29, 2023.
Keywords: Community management; Turubamba; Culture; Citizen participation; Activism